Frequency inborn error of mitochondrial function in Mosul and Kurdistan region: the Frequency inborn error of mitochondrial function in Mosul and Kurdistan region - Abbas, Ashwaq N.; K. Hasan, Mwafak; A. Ahmed, Muhammad (Iraqi Journal of Pharmaceutical Sciences, 2020)
This work aimed to estimate the frequency of mitochondrial inborn errors of metabolism (MIEMs) in patients presenting with family history and IEM-picture who referred for advance IEM assay in Mosul province and Kurdistan region. This study was observational study conducted on 364 cases referred from different general /or private pediatric clinics with unexplained sign and symptoms and suspension of mitochondrial dysfunction. The study included 364 children with an age ranging from 1 month to 1 year. Started from January 2018 to January 2020. All patients referred with their full history review, notes about their clinical examination, and laboratory investigations including blood ammonia, serum lactate/ pyruvate, arterial blood gases. In addition to the standard laboratory-tests (kidney and liver functions, blood glucose, and complete blood picture) carried out in Sorain private Laboratory. The results of this work show that sixteen (4.4%) of cases were positive in the IEM screening test